2013
DOI: 10.1002/ana.23937
|View full text |Cite
|
Sign up to set email alerts
|

Stages of pTDP‐43 pathology in amyotrophic lateral sclerosis

Abstract: Objective To see if the distribution patterns of phosphorylated 43-kDa TAR DNA-binding protein (pTDP-43) intraneuronal inclusions in amyotrophic lateral sclerosis (ALS) permit recognition of neuropathological stages. Methods pTDP-43 immunohistochemistry was performed on 70 μm sections from ALS autopsy cases (N=76) classified by clinical phenotype and genetic background. Results ALS cases with the lowest burden of pTDP-43 pathology were characterized by lesions in the agranular motor cortex, brainstem motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

101
928
3
13

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 867 publications
(1,045 citation statements)
references
References 87 publications
(270 reference statements)
101
928
3
13
Order By: Relevance
“…Family history for ALS was more prevalent in pure bvFTD cases with TDP-43 in the hypoglossal nucleus, but this did not reach significance compared to other bvFTD cohorts (p = 0.06). The recent topographical staging of TDP-43 pathology in bvFTD and ALS [6,7] demonstrated that TDP-43 initiated in the motor system network in ALS is also seen in the majority of bvFTD cases, despite the absence of ALS in over 50% of these [6,21]. In a recent analysis [21], we identified the hypoglossal nucleus as a key brain region in discriminating between cases with and without ALS and the present study corroborates this finding in bvFTD cases.…”
Section: Demographic Featuressupporting
confidence: 88%
“…Family history for ALS was more prevalent in pure bvFTD cases with TDP-43 in the hypoglossal nucleus, but this did not reach significance compared to other bvFTD cohorts (p = 0.06). The recent topographical staging of TDP-43 pathology in bvFTD and ALS [6,7] demonstrated that TDP-43 initiated in the motor system network in ALS is also seen in the majority of bvFTD cases, despite the absence of ALS in over 50% of these [6,21]. In a recent analysis [21], we identified the hypoglossal nucleus as a key brain region in discriminating between cases with and without ALS and the present study corroborates this finding in bvFTD cases.…”
Section: Demographic Featuressupporting
confidence: 88%
“…30 Also, a neuropathologic staging study of TDP-43 in ALS suggests that there is early pathology in motor cortex (stage 1) that spreads to prefrontal cortex (stage 3) and does not reach hippocampus until later in the disease course Table 2 Linear (stage 4). 31 One source of discrepancy of hippocampus decline between the prior imaging study and the current study is that group averages may obscure heterogeneous rates of decline across individuals who are hypomethylated or hypermethylated. Future studies with larger samples are warranted to better understand the association between longitudinal decline and C9orf72 methylation in each individual GM region.…”
mentioning
confidence: 67%
“…In addition to SOD1, 6 TAR DNA-binding protein of 43 kDa (TDP-43) aggregate propagation has been compared with a prion-like seeding mechanism, with evidence of regional spreading of pathology occurring in a sequential pattern through the neuroaxis. 7 Initially, evidence from HEK293 cells suggested that recombinantly produced TDP-43 could trigger aggregation of cell produced TDP-43 after its translocation into the cell, 8 consistent with a seeding reaction. It has also been observed that insoluble TDP-43 from human ALS brain could seed further TDP-43 aggregation in SH-SY5Y cells after its artificial translocation into cells, and that these aggregates could transfer to na€ ıve cells.…”
Section: Introductionmentioning
confidence: 99%